Parental Financial Monitoring and Financial Literacy: The Moderating Effects of Parental Income - Ndou, Adam (Dinasti Publisher, 2023)
The moderating effect of parental income on parental financial monitoring and financial literacy is increasingly becoming important. This study determined whether the relationship between parental financial monitoring and financial literacy is moderated by parental income. Quantitative research approach was adopted. Self-administered questionnaire was used to collect data. Moderated regression analysis was used to analyse data. The results showed that Parental income moderated the relationship of Parental financial monitoring with financial knowledge, financial behaviour, and financial attitude. Furthermore, the results indicated that parental income did not moderate the relationship of Parental financial monitoring and financial decision-making. Therefore, the overall results indicated that the relationship between parental financial monitoring and financial literacy is moderated by parental income. This study is the first to investigate whether the relationship between parental financial monitoring and financial literacy is moderated by parental income. This study concluded by providing recommendations and suggestions for future research.